Serum paraoxonase-1 activity as a novel marker in the diagnosis and prognosis of hyperthyroidism - Kale, Bhagwat (International Journal of Biological Research, 2013)
Thyrotoxicosis or hyperthyroidism is the clinical syndrome caused by an excess of circulating free thyroxine and free triiodothyronine, or both. It was first diagnosed in 1979 in the US. Since this time, the frequency of this diagnosis has increased. It is common, affecting about 2% of women and 0.2% of men. The most common causes of Thyrotoxicosis are Graves' disease and formation of multinodular goiter and autonomously functioning solitary thyroid nodule. In excessive production of thyroid hormones, the basal metabolic rate can be increased by 100%. Hyperthyroidism also induces a hyperdynamic cardiovascular state that is associated with tachycardia, systolic hypertension, atrial fibrillation  and increased cardiovascular mortality. The present study was designed to investigate the relationship among the serum PON-1 activity, lipid profile, and thyroid hormone level in patients with hyperthyroidism. In our research, we have estimated PON 1 activity in hyperthyroidism. We found the PON 1 activity decreased in the hyperthyroid patients  (144.89  ±  3.27 U/ml)  as compared to controls (214.71  ±  5.46 U/ml) significantly (p